Entrepreneurship Education Study: Change Management and Entrepreneurial Dreams - Aristiyanto, Roma (Universitas Adiwangsa Jambi, 2023)
This article aims to elucidate the concept of change management within the realm of education and explores how nurturing entrepreneurial dreams in the field of education can serve as a key to fostering innovation in the educational sphere. The research methodology employed in this article is based on an extensive review of pertinent literature and the analysis of relevant scholarly works to identify the role of change management in education and delve into the influence of entrepreneurial dreams on educational innovation. The findings of this study provide a comprehensive understanding of the concept of change management in education and delineate concrete steps that can be taken to cultivate entrepreneurial dreams in the field of education. Emphasis is placed on the importance of identifying necessary changes, change planning, effective communication, skill development, networking, and overcoming resistance to change in the pursuit of educational objectives.